Role of the microbiota–gut–lung axis in the pathogenesis of pulmonary disease in children and novel therapeutic strategies - Wang, Zhifang; Yu, Jiayao; Liu, Yaqi; Gong, Jiaqi; Hu, Zepeng; Liu, Zheng (Frontiers in Immunology, 2025)
Emerging evidence highlights the microbiota–gut–lung axis (MGLA) as a pivotal regulator of pediatric respiratory health, yet mechanistic insights are lacking and therapeutic applications remain unclear. This review synthesizes cutting-edge findings to delineate how gut microbiota-derived metabolites, particularly short-chain fatty acids (SCFAs), orchestrate pulmonary immunity and disease pathogenesis in children. Leveraging multi-omics integration (metagenomics, metabolomics, transcriptomics), emerging studies have uncovered novel microbe–host interactions driving immune dysregulation in asthma, pneumonia, and cystic fibrosis. A comprehensive map of gut–lung crosstalk has been established across these conditions. Current studies suggest that early-life gut dysbiosis, shaped by delivery mode, antibiotics, and diet, disrupts SCFA-mediated immune homeostasis, amplifying T-helper 2 cell inflammation and impairing alveolar macrophage function. Crucially, we identified disease-specific microbial signatures (e.g., depletion of Lachnospira and Faecalibacterium in asthma) and demonstrated that fecal microbiota transplantation and probiotic interventions restore microbial balance, attenuating airway inflammation in preclinical models. This work pioneers the translation of MGLA insights into precision medicine strategies, highlighting dietary modulation and microbial therapeutics as viable alternatives to conventional treatments. By bridging microbial ecology and immune dynamics, our findings provide actionable biomarkers for early diagnosis and personalized interventions, addressing critical gaps in pediatric respiratory disease management. The integration of multi-omics frameworks not only advances mechanistic understanding but also positions the MGLA as a transformative target in reducing global childhood morbidity. Future research must prioritize longitudinal studies and clinical trials to validate these innovations, ultimately redefining therapeutic paradigms for GLA-driven pathologies.